2021
DOI: 10.1186/s13046-021-01876-z
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation homeostasis controlled by calcium influx channels regulates multiple myeloma dissemination

Abstract: Background Multiple myeloma (MM) cell motility is a critical step during MM dissemination throughout the body, but how it is regulated remains largely unknown. As hypercalcemia is an important clinical feature of MM, high calcium (Ca2+) and altered Ca2+ signaling could be a key contributing factor to the pathological process. Methods Bioinformatics analyses were employed to assess the clinical significance of Ca2+ influx channels in clinical specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…It is generally believed that the BM microenvironment provides support for MM cell growth and survival and for the acquisition of aggressive phenotypes. High Ca 2+ and altered Ca 2+ signals in the BM microenvironment may be a key contributing factor to the pathological process [ 68 ]. Therefore, Ca 2+ channels and transporters, which are molecular participants of Ca 2+ homeostasis, could be significantly involve with MM progression in term of MM cell motility and dissemination.…”
Section: Plasma Membrane Ca 2+ Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally believed that the BM microenvironment provides support for MM cell growth and survival and for the acquisition of aggressive phenotypes. High Ca 2+ and altered Ca 2+ signals in the BM microenvironment may be a key contributing factor to the pathological process [ 68 ]. Therefore, Ca 2+ channels and transporters, which are molecular participants of Ca 2+ homeostasis, could be significantly involve with MM progression in term of MM cell motility and dissemination.…”
Section: Plasma Membrane Ca 2+ Channelsmentioning
confidence: 99%
“…Samart et al observed that the expression of Ca 2+ influx channels (such as TRPM7) in patient-derived MM cells are upregulated compared with normal plasma cells in a bioinformatics database. They used the CRISPR/Cas9 system to repress TRPM7 gene expression in MM cells, which can significantly inhibit the migration and invasion of MM cells [ 68 ]. Such result can reduce the intravasation of MM cells from the BM into nearby blood vessels and for their subsequent extravasation into distant tissues [ 69 , 70 ].…”
Section: Plasma Membrane Ca 2+ Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Public databases suggest O-GlcNAcylation is actually reduced in myeloma as OGA was significantly higher in 133 primary myeloma samples compared to normal plasma cells from 5 normal donors with similar OGT expression ( 184 , 185 ). Myeloma microenvironments contain high levels of calcium released by osteolysis.…”
Section: O-glcnacylation In Other Hematological Malignanciesmentioning
confidence: 99%